Le Traitement Médiatique du Transfèrement de Laurent Gbagbo à la Haye Par Trois Quotidiens Ivoiriens Entre 2011 et 2012 - Gnonzion, Celestin (European Scientific Journal, ESJ, 2017)
This article aims to highlight the problems that are associated with a number of Ivoirian press. In the newsrooms, journalists basically handle information on the subject of politics with partiality. For instance, in the news coverage of the transfer of former President Laurent Gbagbo to The Hague, this paper shows how this fact was dealt with in three newspapers: ’Notre Voie’, ’Le Nouveau Reveil’, and ’Le Patriote’. Each of these newspapers treated the information according to the perception of leaders and politicians they want to satisfy. The article demonstrates that when the owner of the journal is influenced by politic power, it is difficult to have professionals in journalism who respect the journalist’s code of ethic and deontology.